Selective C−H Halogenation with a Highly Fluorinated Manganese Porphyrin. (28th December 2017) - Li, Gang; Dilger, Andrew K.; Cheng, Peter T.; Ewing, William R.; Groves, John T.
Abstract: The selective C−H functionalization of aliphatic molecules remains a challenge in organic synthesis. While radical chain halogenation reactions provide efficient access to many halogenated molecules, the use of typical protocols for the selective halogenation of electron‐deficient and strained aliphatic molecules is rare. Herein, we report selective C−H chlorination and fluorination reactions promoted by an electron‐deficient manganese pentafluorophenyl porphyrin catalyst, Mn(TPFPP)Cl. This catalyst displays superior properties for the aliphatic halogenation of recalcitrant, electron‐deficient, and strained substrates with unique regio‐ and stereoselectivity. UV/Vis analysis during the course of the reaction indicated that an oxo‐Mn V species is responsible for hydrogen‐atom abstraction. The observed stereoselectivity results from steric interactions between the bulky porphyrin ligand and the intermediate substrate radical in the halogen rebound step.